Evaluation Of Nutritional Content And Antioxidant Activity In Ku Cake With Different Natural Colors - Sari Mustika; Anni Faridah; Ranggi Rahimul Insan (Jurnal Sains dan Teknologi Pangan, 2025)
Kue Ku produced with various natural colors will have their nutritional content and antioxidant activity tested in this research. Processing Kue Ku with a variety of natural dyes—including purple sweet potato, dragon fruit, black rice, and yellow pumpkin—was the focus of this investigation. The DPPH technique was used to test antioxidant activity, and the nutritional composition that was examined included water, ash, fat, protein, and carbohydrates. Dragon fruit, purple sweet potato, yellow pumpkin, and black rice were the Kue Ku varieties with the greatest and lowest water content, respectively. In order of ash content, the following Kue Ku varieties were found: Yellow Pumpkin, Kue Ku Black Rice, Kue Ku Purple Sweet Potato, and Kue Ku Dragon Fruit. From most fattening to least, these Kue Ku varieties are as follows: Yellow Pumpkin, Dragon Fruit, Purple Sweet Potato, and Black Rice. Purple sweet potato Kue Ku, yellow pumpkin Kue Ku, black rice Kue Ku, and dragon fruit Kue Ku were the varieties with the greatest and lowest protein contents, respectively. Kue Ku Dragon Fruit, Kue Ku Pumpkin, Kue Ku Sweet Potato Purple, and Kue Ku Black Rice are the varieties of Kue Ku that range in carbohydrate content from highest to lowest. Kue Ku Sweet Potato Purple has the lowest antioxidant activity, whereas Kue Ku Pumpkin Yellow has the greatest.